Avocado and soybean extracts as active principles in the treatment of mild‐to‐moderate vulvar lichen sclerosus: results of efficacy and tolerability. (3rd September 2014) - Borghi, A.; Corazza, M.; Minghetti, S.; Toni, G.; Virgili, A.
Abstract Objective Limited evidence is available on the effectiveness of treatments alternative to corticosteroids for vulvar lichen sclerosus (VLS). The present study aimed to assess the efficacy and tolerability of avocado and soybean extracts (ASE) as active principles of both a topical product and a nutritional supplement in the treatment of active mild‐to‐moderate VLS. Materials and methods Twenty‐three patients were enrolled. Treatment consisted of a topical product containing ASE and other lenitive and anti‐oxidant principles administered twice daily for 24 weeks, in association with a dietary supplement containing ASE, vitamin E and para‐aminobenzoic acid for the first 12 weeks. The primary efficacy endpoint was the rate of patients achieving an improvement from baseline in global subjective score (GSS) and global objective score (GOS) of ≥ 75%. Secondary efficacy endpoint was the rate of patients achieving GSS50 and GOS50. Tertiary efficacy endpoint was the mean reduction in subjective and objective scores throughout the treatment. Results By the end of the 24‐week treatment, 12 (70.5% of symptomatic patients) and 13 patients (72.2%) achieved an improvement of at least 75% in subjective and objective global scores, respectively; 100% and 88.9% reached GSS50 and GOS50, respectively. Mean symptom and sign scores decreased significantly after treatment. The treatment was well tolerated. Conclusions Our results provide evidence that the topical and dietary supplements used in the study, which contain active principles exerting anti‐inflammatory, anti‐fibrotic, emollient and lenitive actions, are effective alternatives in the treatment of symptoms and signs of mild‐to‐moderate VLS.